Auditory characteristics and balance function of diabetic patients - Hlayisi, Vera-Genevey (Division of Communication Sciences and Disorders, 2017)
Aims and Objectives. This study aimed to describe auditory characteristics and balance function in patients with diabetes between 18-55 years of age as well as determine the association between patients' auditory and balance function with diabetes characteristics (type, duration and control). Background. Diabetes is one of the most prevalent non-communicable diseases worldwide with approximately 422 million people diagnosed globally. This number is projected to rise to 642 million by 2040 if no appropriate interventions are implemented to reverse the rise in the number of people with diabetes. South Africa has the second highest diabetes prevalence in Africa (after Nigeria) with 2.6 million cases. A rise in diabetes prevalence should be a concern for audiologists with increasing literature linking diabetes with the risk of acquiring hearing and balance disorders. However, there is currently a lack of research done in South Africa to investigate auditory and balance disorders in patients with diabetes. Therefore, the current study sought to investigate auditory characteristics and balance function in South African patients diagnosed with diabetes. It is anticipated that the study findings will yield evidence that will highlight the role of an audiologist in the clinical management of patients with diabetes. Research Design. The study utilised an observational cross-sectional matched groups design with a cohort (patients with diabetes) and control (volunteers without diabetes) group of participants. Participants were recruited from a Primary Health Care clinic in Polokwane, Limpopo using purposive and convenience sampling for the cohort and control group respectively. Methodology. Several methods were used to collect data pertinent to this study. These included case history interview and a medical folder review to obtain information related to participants' diabetes status. Furthermore, all participants underwent the following assessments: otoscopy, pure tone audiometry, diagnostic distortion product otoacoustic emissions (DPOAE), vision screening, peripheral neuropathy screening, Dynamic Gait Index test (DGI) and the Modified Clinical Test of Sensory Integration (MCTSIB). Data were analyzed using both descriptive and inferential statistical tests. Results. A total of 192 participants took part in this study; 110 in the cohort and 82 in the control group. There were similar distributions of gender in both groups with the following age distributions (in years) for each group; cohort; median =46, range =20-55, control; median =43, range =21-55. Pure tone audiometry assessments showed a significantly higher prevalence of hearing loss in the cohort (55%) when compared to the control (20%) group (p < .001). Participant age, gender and diabetes duration were associated with the likelihood of having hearing loss (age: odds ratio=2.90, 95% CI: 1.19-7.08, p=0.019; gender (male): odds ratio=.266, 95% CI: .104-.677, p=0.005; diabetes duration: odds ratio=1.12, 95% CI: 1.02-1.22, p=0.013). DPOAE assessments showed significantly higher percentages of abnormalities with signal to noise ratio (p < 0.01) and DPOAE level (p < 0.01) in the cohort compared to the control group. A significantly higher proportion (38%) of participants in the cohort group reported tinnitus when compared to 15% in the control (p < .001). Balance screening assessments with the DGI and the MCTSIB, showed significantly poorer performance in the cohort group than the control (DGI:, p < .001; MCTSIB: p < .001). Conclusion. Overall findings of this study showed that participants who were diagnosed with diabetes had a higher proportion of auditory and balance abnormalities when compared to those in the control group. Older age, male gender and longer duration since diabetes diagnosis were associated with a higher likelihood of having hearing loss. The findings of this study therefore suggest that auditory and balance dysfunction should be considered as comorbidities associated with diabetes. This study also highlighted the role of an audiologist in the managment of patients with diabetes with respect to early identification and management of auditory and balance dysfunctions amongst these patients.